Influence of the texture on the efficiency of thermal desorption process of soils contaminated with crude oil - Pop Dorina (Review on agriculture and rural development, 2014)
The hereby paper presents the experimental research on the influence of three types of soil texture on the efficiency of decontamination performed using the technology of thermal desorption. The concentrations of crude oil of the soil samples, the initial ones as well as those following the depollution process were determined using the Soxhlet method. The decontamination process with thermal desorption on soil samples was performed using the electric oven with chamber, and with silicon carbide bars. Experimental researches were performed on the following types of soils: loamy sand, loam and loamy clay. The main parameters established for the process of thermal desorption were the temperature 350 °C and the amount of time for keeping the soil samples in the oven, of 5, 10 and 15 minutes. The results of the experiments indicated that the type of texture has influenced the efficiency of the thermal desorption, and the highest efficiency was obtained for the sample of loamy sand, treated for 15 minutes.